"ANALYSING THE ROLE OF STANDARD SERVICE QUALITY IN FRONT OFFICE OF FIVE STAR HOTELS" - Sameer Mankame; Kishor Vinayak Mhaske (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The link between delivery and client happiness is service quality. The desire to stay in the hotel industry is strong and on behalf of the PLA hotel, they are doing (or making) tremendous efforts. The psychological relationship of the individual to the business of the hotel is also termed. The study established four criteria for service quality, which focused on the front-office staff exclusively and evaluated customer expectations and perception of these services. The results of this assessment may help us get insight into how consumers classify the quality of service and measure our customers’ satisfaction.